Analysis of student problem solving skills on physics concepts in SMP/MTs through blended learning early teaching during the covid-19 pandemic. Issue 1 (April 2021) - Hasan, M; Mursalin,; Odja, A H
Abstract: This study aims to determine students' problem solving skills in physics concepts at the SMP/MTs level by teaching blended learning. The research method used was a mixed method with a sequential explanatory strategy. The data were obtained through the provision of problem-solving tests, the data was strengthened by interviews with student representatives who obtained high, medium and low scores. The sample in this study were 20 students of class VIII of the MTs in Gorontalo. The results of the analysis show that the problem solving ability of physics concepts on the topic of light is in the low category. The average percentage of students' problem solving abilities was 52, 58%. For each problem solving indicator, the percentage is as follows: 72, 50% for the problem focus indicator; 14.66% for physical description indicators; 64.50% for indicators planning completion; 54.75% for indicators of implementing the plan; and for indicators evaluating the completion reached 56.50%. From the results of the interview, there were various obstacles experienced by students in conducting online teaching. Online teaching is carried out using blended learning, namely through virtual face-to-face and non-virtual face-to-face. The low problem solving skills of students for the concept of physics on the topic of light needs to be improved in the application of blended learning, especially related to the obstacles faced by students in implementing blended learning during the Covid-19 pandemic.